Hominoid arcade shape: Pattern and magnitude of covariation. Issue 107 (June 2017) - Stelzer, Stefanie; Gunz, Philipp; Neubauer, Simon; Spoor, Fred
Abstract: The shape of the dental arcade and canine size distinguish extant humans from all apes. Humans are characterized by a parabolic arcade with short postcanine tooth rows and small canines, whereas apes have long, U-shaped arcades with large canines. The evolutionary and biomechanical mechanisms underlying arcade shape differences between and within groups are not well understood. It is unclear, for example, whether evolutionary changes in the covariation among modules comprising the upper and lower jaws are the cause and/or consequence of different arcade shapes. Here we use 3D geometric morphometric methods to explore to what extent the morphological differences in arcade shape between living hominoids are related to differences in covariation of upper and lower jaws, and the premaxilla and the maxilla. We show that all extant hominoids follow a very similar covariation pattern between upper and lower dental arcades, as well as between the premaxilla and the maxilla. We find comparably high magnitudes of covariation between the premaxilla and the maxilla in all groups. Between the upper and lower jaws, levels of covariation are similar in apes ( Pan, Gorilla, Pongo, and Hylobates ), but overall lower in extant humans. Our results demonstrate an independence of the pattern of arcade shape covariation from dental spatial arrangements. Importantly, we show that a shared hominoid pattern of covariation between premaxilla and maxilla together with the covariation of upper and lower jaw is consistent with major evolutionary arcade shape changes in hominoids. We suggest that with the reduction of canine and diastema size in hominins, the incisors move posteriorly and the tooth row becomes more parabolic. Our study provides a framework for addressing questions about fossil hominin dentognathic diversity, including inter- and intraspecific variation and associations of upper and lower jaw morphology.